An investigation on the strength of axially loaded cold-formed steel Z-sections - De Jesus, James Matthew L. (Animo Repository, 2018)
Cold-formed steel (CFS) provides high strength-to-weight ratios that prove efficient in the construction of steel structures. CFS Z-section members exhibit buckling failures that may be difficult to predict due to complexity in geometry. There exists a gap in experimental and computational studies done in the Philippines regarding the structural performance of locally-produced CFS members. The objective of this study is to investigate the load-carrying capacity of Z-section CFS members when subjected to axial compression using experimental and computational methods. The study considers a total of 180 member samples with one section shape, six different lengths and six different thicknesses. Experimentally, the CFS members were subjected to compression loads using a standing steel frame with a hydraulic jack, a load cell and 4 displacement transducers to record the parameters needed for the investigation. High-speed video recordings were used to verify the different failure modes. These are then compared to computational results as per the National Structural Code of the Philippines (NSCP). Furthermore, the study also provides a comparison of experimental and computational results with Finite Element Method (FEM) using ANSYS. The main failure modes were torsional-flexural and distortional buckling. Torsional-flexural buckling was observed in 74.01% of the samples. Although 72.88% of the failure modes were predicted correctly, it was found that the provisions in the NSCP in predicting the strength of the member were relatively high with respect to the experimental and FEM results. This means that the predicted strength was non-conservative. It was also found that a modification factor of 0.52 can be used to achieve similar results between the predicted and actual strength of the member. © Int. J. of GEOMATE.